EFEKTIVITAS SISTEM ONLINE SINGLE SUBMISSION TERHADAP KEMUDAHAN PENGURUSAN IZIN USAHA: (Studi pada Pelaku UMK di Kabupaten Bolaang Mongondow Utara) - Mohamad Fadly Binolombangan (Universitas Bina Taruna Gorontalo, 2024)
This research aims to analyze the effectiveness of the Online Single Submission (OSS) System in facilitating easy business permit processing in North Bolaang Mongondow Regency. OSS is a government initiative designed to simplify the licensing process and encourage investment by integrating various licensing services into one online platform. Through qualitative and quantitative approaches, this research evaluates the extent to which OSS has improved efficiency, transparency and accountability in the business licensing process. The results of the research show that the implementation of OSS has succeeded in reducing the time and costs required to process business permits, as well as increasing user satisfaction, namely micro and small business actors, with government services, especially at the Investment and One-Stop Integrated Services Service (PMPTSP) of North Bolaang Mongondow Regency. . However, this research also found several challenges, such as a lack of user understanding of OSS systems and uneven technological infrastructure. These findings provide important insights for governments and other stakeholders in improving policies and infrastructure to support OSS effectiveness in the future.